32nd Aerospace Sciences Meeting and Exhibit 1994
DOI: 10.2514/6.1994-804
|View full text |Cite
|
Sign up to set email alerts
|

Close-up analysis of inflight ice accretion

Abstract: The objective of this effort was to validate in flight, data that has been gathered in the NASA Lewis Research Center' s Icing Research Tunnel (IRT) over the past several years. All data was acquired in flight on the NASA Lewis Research Center' s Twin Otter Icing Research Aircraft. A faired 3.5 in. diameter metal-clad cylinder exposed to the natural icing environment was observed by a close-up video camera The grazing angle video footage was recorded to S-VHS video tape and after the icing encounter, the resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 2 publications
(1 reference statement)
0
9
0
Order By: Relevance
“…The Reynolds numbers (based on the airfoil chord) tested were 0.75x10 6 , 1.25x10 6 and 2.25x10 6 . The extent of the distributed roughness was 0.125", 0.250" and 0.5" at locations of 4,7,8,12,18, and 24 mm from stagnation. His measurements showed that transition begins at, or very near the trailing edge of the roughness.…”
Section: Effect Of Large Roughness Elements On Boundary Layer Devementioning
confidence: 96%
See 1 more Smart Citation
“…The Reynolds numbers (based on the airfoil chord) tested were 0.75x10 6 , 1.25x10 6 and 2.25x10 6 . The extent of the distributed roughness was 0.125", 0.250" and 0.5" at locations of 4,7,8,12,18, and 24 mm from stagnation. His measurements showed that transition begins at, or very near the trailing edge of the roughness.…”
Section: Effect Of Large Roughness Elements On Boundary Layer Devementioning
confidence: 96%
“…They also observed that since feathers tended to spread out laterally, when the feather density is high, adjacent feathers will tend to merge. Reehorst et al 12 used the same experimental setup for close-up in-flight observations in the NASA Glenn Research Center's Twin Otter Icing Research Aircraft. They measured the effect of droplet size and water flux on the feather growth rate.…”
mentioning
confidence: 99%
“…As the feathers grow, not only do they distort the oncoming and downstream flow, but they also constitute an added impingement region that protrudes into the flow. Therefore, droplets that bypass the stagnation area can be important due to their contribution to ice growth downstream [4]. This shows clear evidence for the necessity of accurate droplet trajectory calculations and for the importance of completeness of the water transport models.…”
mentioning
confidence: 89%
“…The MVD for these droplets can be on the order of 100 m. These droplets do not comply with the aforementioned assumptions and cause unpredictable ice shapes due to different underlying mechanisms. An example of the unpredictable features of the resultant ice shapes is the feather growth, which takes place beyond the calculated impingement region [4]. As the feathers grow, not only do they distort the oncoming and downstream flow, but they also constitute an added impingement region that protrudes into the flow.…”
mentioning
confidence: 99%
“…-Droplet shape distortion leading to a different drag force, hence different path, than expected 33 , -Droplet break-up before impingement 33 , -Splashing, re-impingement and consequent water redistribution 34 , -Water film dynamics 12 , -Impact on heat transfer characteristics, and -Ice sublimation 35 .…”
Section: Chapter IV Mechanisms For Downstream Ice Growthmentioning
confidence: 99%